Expose Application: A Development of Learning Media For Optimising Young Learners’ English Vocabulary - Setiawan, Galuh Sekararum; Widayati, Sri; Adhe, Kartika Rinakit; Saroinsong , Wulan Patria (Elsya : Journal of English Language Studies, 2023)
The need for English language proficiency in this age of globalisation demands a variety of efforts to learn the lingua franca as soon as possible. The use of media is one of the teaching strategies that kindergarten teachers could employ to maximise the interests and desires of the students in English learning. This study aims to describe the development of process design and validation of a proposed learning media called ‘Expose’, which is empirically tested with a limited group. ‘Expose’ is the media that was developed to meet the needs of vocabulary learning at the level of early childhood education. This type of research is R&D (Research and Development) using the ASSURE model. Validation of the content and media expert shows that ‘expose’ is being ‘very good’ for stimulation vocabulary for early childhood. Furthermore, empirical tests on a limited group (20 children aged 5-6 years in Lampah, Gresik) The study revealed that using the Expose application media to teach English vocabulary to kids between the ages of 5 and 6 significantly altered learning outcomes. The results of this research underscores how kindergarten teachers must be especially careful in choosing the appropriate vocabulary and learning technology for young children to learn.